PENGARUH BEBAN KERJA, MOTIVASI KERJA, DAN LINGKUNGAN KERJA TERHADAP TURNOVER INTENTION KARYAWAN DI 5 (LIMA) UNIT PT BANK RAKYAT INDONESIA (PERSERO) TBK KOTA TANGERANG SELATAN - Hawa Riyanti Utami (2022)
This study is a quantitative study to determine the effect of workload, work motivation, and work environment on turnover intention. This research is motivated by the phenomena found in 5(Five) units of PT Bank Rakyat Indonesia (Persero) Tbk regarding workload, work motivation, work environment and work discipline. The sample used in this study is a saturated sample of 45 employees in 5 (Five) units of PT Bank Rakyat Indonesia (Persero) Tbk. The analysis technique used is path analysis and data processing carried out through SmartPLS 3.0. The results obtained from this study are (1) workload has a positive and significant effect on employee turnover intention in 5(Five) units of PT Bank Rakyat Indonesia (Persero) Tbk. (2) work motivation has a negative and significant effect on employee turnover intention in 5 (Five) units of PT Bank Rakyat Indonesia (Persero) Tbk. (3) The work environment has a negative and significant effect on employee turnover intention in 5 (Five) units of PT Bank Rakyat Indonesia (Persero) Tbk.